The SAGE handbook of education for citizenship and democracy - Hahn, Carole; Arthur, James 1957-; Davies, Ian 1957- (Los Angeles, [California] London SAGE, 2008)
This handbook brings together new work by some of the leading authorities on citizenship education, and is divided into five parts
Title from title screen (viewed October 19, 2023)
Includes bibliographical references and index
Keywords: Democracy and education -- Cross-cultural studies; Citizenship -- Study and teaching -- Cross-cultural studies